Growth of the [110] Oriented TiO2 Nanorods on ITO Substrates by Sputtering Technique for Dye-Sensitized Solar Cells - Meng, Lijian; Chen, Hong; Li, Can; dos Santos, Manuel Pereira (Frontiers in Materials, 2014)
TiO2 films have been deposited on ITO substrates by dc reactive magnetron sputtering technique. It has been found that the sputtering pressure is a very important parameter for the structure of the deposited TiO2 films. When the pressure is lower than 1 Pa, the deposited film has a dense structure and shows a preferred orientation along the [101] direction. However, the nanorod structure has been obtained as the sputtering pressure is higher than 1 Pa. These nanorods structure TiO2 film shows a preferred orientation along the [110] direction. The phases of the deposited TiO2 films have been characterized by the x-ray diffraction and the Raman scattering measurements. All the films show an anatase phase and no other phase has been observed. The results of the SEM show that these TiO2 nanorods are perpendicular to the ITO substrate. The TEM measurement shows that the nanorods have a very rough surface. The dye-sensitized solar cells (DSSCs) have been assembled using these TiO2 nanorod films prepared at different sputtering pressures as photoelectrode. And the effect of the sputtering pressure on the properties of the photoelectric conversion of the DSSCs has been studied.